A taxonomy of microservice integration techniques - Schwarz, Georg-Daniel; Bauer, Andreas; Riehle, Dirk; Harutyunyan, Nikolay (Information and Software Technology, 2025)
Context: Microservices have become an important architectural style for building robust and scalable software systems. A system’s functionality is split into independent units, the microservices, that communicate over a network and can be deployed independently. The shift of complexity into the integration layer necessitates enhanced collaboration among stakeholders, stressing the importance of effective communication. Objective: We aim to streamline communication between stakeholders in microservice-based projects by constructing a framework for enhanced clarity, a taxonomy, by answering our research question: “How can microservice integration techniques be classified?” Method: We conducted a thematic analysis of literature and six expert interviews to identify microservice integration techniques and construct a taxonomy. Results: The results of this study are (i) a taxonomy for microservice integration techniques consisting of five main and ten refined categories, (ii) the classification of 121 found integration techniques, (iii) an illustration of the taxonomy usage based on three selected techniques to demonstrate the procedure in case of classification ambiguity, (iv) a comparison of data gathered from literature with the interviews, and (v) comprehensive supplementary materials. Conclusion: The taxonomy offers a structured framework to classify microservice integration techniques and enhances the understanding of the diverse landscape of microservice integration techniques, including organizational ones that are often overlooked. Practitioners can discover integration techniques through the taxonomy and apply them with guidance provided in the supplementary materials.
Keywords: Microservices; Integration; Techniques; Taxonomy